METHODS FOR THE RATIONAL USE OF NATURAL RESOURCES AND THE STUDY OF GEOGRAPHICAL TOURISM IN THE FERGANA VALLEY - Odiljon Tobirov; Xidoyatkhon Abdinazarova; Azamjon Jobborov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This review paper examines the methods for the rational use of natural resources and the development of geographical tourism in the Fergana Valley, a region characterized by high ecological diversity, rich cultural heritage, and increasing anthropogenic pressure. Based on a comprehensive analysis of interdisciplinary scientific literature, the study explores the interactions between natural resource management, tourism development, and local community involvement. Particular attention is paid to sustainable tourism concepts, eco-tourism models, and participatory approaches that integrate ecological, economic, and socio-cultural dimensions. The findings indicate that rational resource use—especially of water, land, and landscape resources—is a key prerequisite for maintaining environmental balance while ensuring the long-term viability of the tourism sector. The review also identifies significant research gaps related to localized environmental impacts of tourism and community perceptions of resource use. The paper concludes that the integration of GIS-based methods, stakeholder participation, and sustainability frameworks is essential for formulating effective policies aimed at balancing environmental conservation with socio-economic development in the Fergana Valley.